Disorders of sex development a guide for parents and physicians - Amy B Wisniewski; Steven D Chernausek; Bradley P Kropp (Baltimore : The Johns Hopkins University Press, 2012)
This book offers families essential information about the causes, diagnosis, and treatment of disorders of sex development, or DSD.